RISK FACTORS ASSOCIATED WITH PRECANCEROUS LESION - Lutfiana Kusumaningrum; Sa’adah Mujahidah; Melyana Nurul Widyawati; Bahiyatun Bahiyatun (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Background: Visual inspection acetic acid (VIA) can be a substitute method for early detection of Precancerous lesion of cervical cancer. Therefore, efforts should be made for prevention to increase community awareness in recognizing the risk factors of cervical cancer so that it can determine the steps of prevention and early detection. Aims: This research is to determine the risk factors associated with precancerous lesion, a study case- control in Health Center of Semarang City Year 2016). Methods: This research is an observational analytic study with case-control design with retrospective study. The sample selection was using a simple random sampling method. The number of respondents is 98 people from 474 people doing the VIA inspection in January 2016 to December 2016, which passed the inclusion and exclusion criteria and divided into two groups, 13 people in case and 86 people in control group. Results: There is a relationship between the results of the examination of the precancerous lesion with the risk factor of the number of respondent marriages (P- 0.038), husband historical marriage (P-0.000), smoking exposure (P-0.000). Conclusion: Risk factors associated with the results of the examination precancerous lesion are the number of responden marriages, husband historical marriage, smoking exposure.